Who are the fairest? ethnic segmentation in London's media production. (1st January 2007) - Ashika Thanki,; Steve Jefferys,
Abstract : London is a global media city where over 30 per cent of the workforce is from black and ethnic minorities. Yet only seven per cent of those in media production come from these minorities, and they are concentrated in lower level and non-mainstream jobs. The authors argue that the anachronistic survival of institutional racism is not simply about the survival of a discriminatory 'monoculture'. While racism is enabled by the major casualisation of the industry, it is also functional, helping to defend a stable process of elite formation and defence in a key area of capitalist ideological production. This racism is about power and the authors' research into why ethnic minority professionals quit London's media production sector also explains how this power imbalance deters resistance.